International Corporate Law - Volume 1. - Macmillan, Fiona (Bloomsbury Publishing, 2000)
The International Corporate Law series is dedicated to the publication of scholarly writing on issues in the area of internaional and comparaticve corporate law. Each volume is dividedinto two parts. The first part contains essays focusing on theoretical issues in corporate law, comparative corporate law topics, or supranational issues in corporate law. The second part of the volume contains selected short country reports. This the inaugual volume in the series, contains contributions fromm scholars in Australia, Japan, Nigeria, the United Kingdom and the United States, writing on a wide range.